Advances in canoe technique from Sydney to London - Suarez Amador, N. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
An ideal model of a sports movement, defined by scientific knowledge and practical experience (Grosser and Neumaier, 1986). Form when performing an exercise. The more perfect the technique, the less energy needed for the desired result. (Bompa, 1983).Technique is the most rational and the most effective way of performing exercises (Ozolin, 1983). Physical and technical preparation of the basis of sports performance. With a good physical preparation, tactical concepts are introduced. With a good level of all factors, psychological preparation determines the best outcome. From a technical point of view, canoeing is framed within the so-called "cyclic resistance sports" (Merni, 1991). That is why technique will allow us to perform the movement in the most economic form possible, delaying the fatigue. If this cyclic movement is produced in "continuous" form, we can study it repetitively and divide it in phases and sub-phases, and we can appreciate the possible errors in accordance with an established model. During technical execution, fatigue leads to errors, which either increases or decreases fatigue. This is why it is very important to study and learn the appropriate techniques. Analysis will lead to a more detailed knowledge of the paddle's technical movement, which will help us to design the training methodology and the usage of the material (media) for improvent in performance. Qualitative analysis involves discovering, decomposing, dividing, observing or isolating the composing elements of the sports technique. It can be used during observation, and when the qualitative analysis is completed, a subjective evaluation may follow. Relations are also established with the material, the surroundings, the mobility, the opponent etc. Its effectiveness increases with the use of systematic processes, and the precision of the observation is improved with the registry of images (video, high speed cameras) such as that obtained with photo seriation (figure 2). The performance, or a certain aspect of it such as the trajectory of the support of the paddle in the water, are registered using a reliable enough procedure (such as a vectorial decomposition) (Fig. 3). The use of quantitative methods facilitates the objective evaluation, and it helps in defining the parameters that will facilitate the qualitative analysis.